(untitled) (Лучшие интеллектуальные исследования, 2025)
ANNOTATION: This article will analyze the reforms carried out in the field of physical education and sports in the framework of the development strategy for 2022-2026 in the Republic of Uzbekistan, their role in youth education, the role of sports in socio-economic development and the tasks in the future.